2004
DOI: 10.1016/j.jhsb.2004.06.004
|View full text |Cite
|
Sign up to set email alerts
|

An Objective Method to Evaluate the Risk of Recurrence and Extension of Dupuytren’s Disease

Abstract: This study was undertaken to assess the influence of the factors related to Dupuytren's diathesis on the rates of recurrence and extension of Dupuytren's disease after surgery. The records of 65 patients who underwent surgery for Dupuytren's disease were retrospectively studied and the presence of factors related to diathesis were recorded. The sensitivity and specificity of each factor for predicting recurrence and extension were calculated. Odds ratios and 95% confidence intervals were also calculated and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 10 publications
4
67
1
3
Order By: Relevance
“…The variables associated with poorer outcome in this study differ from those identified as contributing to the Dupuytren's diathesis in other studies (Abe et al, 2004;Hindocha et al, 2006;Hueston, 1963). This suggests that those patients whose hand function is worse following surgery may not always be the patients who experience recurrence.…”
Section: Functional Outcomecontrasting
confidence: 83%
See 1 more Smart Citation
“…The variables associated with poorer outcome in this study differ from those identified as contributing to the Dupuytren's diathesis in other studies (Abe et al, 2004;Hindocha et al, 2006;Hueston, 1963). This suggests that those patients whose hand function is worse following surgery may not always be the patients who experience recurrence.…”
Section: Functional Outcomecontrasting
confidence: 83%
“…One randomized controlled trial reported a reoperation rate within 5 years of 33/52 (63%) for aponeurotomy and 4/41 (9%) for fasciectomy . Whereas their reoperation rate for aponeurotomy was two times greater than that in our study, their reoperation rate after fasciectomy was similar to ours (6%) Abe and colleagues investigated the factors associated with reoperation at a mean follow-up of 5 years in a small Japanese population (Abe et al, 2004). They found that the factors in the classical diathesis had prognostic value.…”
Section: Objective Outcomessupporting
confidence: 77%
“…Dupuytren's diathesis also was evaluated by obtaining a thorough family history and asking about ectopic fibrosis (Ledderhose's plantar fibrosis or Peyronie's penile fibrosis). The individual scores of Abe et al [1] were calculated, with a score greater than 4 representing a high recurrence risk. Attention also was focused on the total number of operations and the most extensive surgical technique used in each patient (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…A couple attempts to predict recurrence or extension of Dupuytren's disease (DD) by developing scoring systems such as that of Abe et al [1] have been made, with predictive risk values ranging from 23% to 71% [1,10]. Such risk scores are based on clinical features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation